2021
DOI: 10.1371/journal.pone.0252571
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics analysis of N-acetyl-D-glucosamine against specific SARS-CoV-2’s pathogenicity factors

Abstract: The causative agent of the pandemic identified as SARS-CoV-2 leads to a severe respiratory illness similar to SARS and MERS with fever, cough, and shortness of breath symptoms and severe cases that can often be fatal. In our study, we report our findings based on molecular docking analysis which could be the new effective way for controlling the SARS-CoV-2 virus and additionally, another manipulative possibilities involving the mimicking of immune system as occurred during the bacterial cell recognition system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The sugars most often associated with glycoprotein uptake of viruses are sialic acid, N-acetylglucosamine, N-acetylgalactosamine, mannose, and fucose ( Shilatifard et al, 1993 , Ushijima et al, 1992 ), with evidence that sialic acid and N-acetylglucosamine are involved in S1 binding and SARS-CoV-2 uptake ( Baysal et al, 2021 , Nguyen et al, 2022 ). Here we used lectins selective for these sugars (WGA: sialic acid and N-acetyl-D-glucosamine, LEL: N-acetylglucosamine and N-acetylgalactosamine, LTL: fucose arabinose, RCA: N-acetylgalactosamine and N-acetylglucosamine, GNL: mannose, SNA: sialic acid) to determine which were most likely to be involved in I-S1 transport across the BBB and uptake by peripheral tissues ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The sugars most often associated with glycoprotein uptake of viruses are sialic acid, N-acetylglucosamine, N-acetylgalactosamine, mannose, and fucose ( Shilatifard et al, 1993 , Ushijima et al, 1992 ), with evidence that sialic acid and N-acetylglucosamine are involved in S1 binding and SARS-CoV-2 uptake ( Baysal et al, 2021 , Nguyen et al, 2022 ). Here we used lectins selective for these sugars (WGA: sialic acid and N-acetyl-D-glucosamine, LEL: N-acetylglucosamine and N-acetylgalactosamine, LTL: fucose arabinose, RCA: N-acetylgalactosamine and N-acetylglucosamine, GNL: mannose, SNA: sialic acid) to determine which were most likely to be involved in I-S1 transport across the BBB and uptake by peripheral tissues ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, the initial infection of SARS‐CoV‐2 can trigger, but might not directly involve massive inflammatory responses, and therefore glucosamine use does not alter the susceptibility to COVID‐19 positivity. In addition, previous research confirmed that N‐acetyl‐ d ‐glucosamine, the acetylated derivative of glucosamine, held the potential to suppress several SARS‐CoV‐2 proteins, and induced an immune response against the virus in the host 40 . Moreover, glucosamine has been shown to promote the formation of other structures within various extracellular matrices (ECMs) 41 .…”
Section: Discussionmentioning
confidence: 88%
“…l ‐Gulose is a particularly important rare sugar, as it is the sugar moiety to serve as a key building block for the preparation of the broad‐spectrum anticancer drug bleomycin and l ‐nucleoside‐based antiviral agents 36 . In addition, N ‐acetyl‐ d ‐galactosamine from Agaricus bisporus possesses anti‐tumour and immunomodulating activities, and N ‐acetyl‐ d ‐glucosamine can inhibit several SARS‐CoV‐2 proteins and induce an immune response against the virus in the host 37,38 . Amino acids serve as the basic component unit of proteins and participate in the composition of enzymes, hormones, and vitamins, playing a crucial role in regulating physiological function and catalysing metabolism 39,40 .…”
Section: Discussionmentioning
confidence: 99%